(untitled) (MAUSAM, 1965)
The study reveals that in the computation of pan evaporation the use of the energy term becomes very important under condition of high evaporation. A procedure for computation of solar radiation for a close network of stations from the percentage hours of sunshine has been outlined. Kohler’s technique for deriving pan evaporation using solar radiation, total wind run, average air temperature and vapour pressure data has been found to yield good results under Indian conditions- Monthly normal evaporation maps using Kohler’s technique have been prepared and discussed.